Visiting Albert and Rose Watkins And Friends in Southern California - Watkins, Howard::::::::: (1983)
Pat Motts, saleslady, Rose Watkins, Yuki Hayashi, Adam Watkins, Christine Watkins holding Robin Watkins in front of the Juvenile Shop Located at 4402 W. Pico Blvd., Los Angeles; corner of S. Windsor Blvd.